Curricularização da extensão: sugestões para a implantação no curso de administração da Unipampa - Fros, Carmen Lia Remedi (2017)
The university extension programs have becoming noticeable in the academic field. They are the supporter of the transforming interaction between University and society, and thus the programs have become institutionalized through many laws since 1931. Therefore, in 1988 the indissolubility of research, teaching and extension in universities are included as a Constitutional principle. The National Plan for Education (2014-2024) is a public policy which through 12.7 strategy aims at ensuring at least 10% of credits concerning graduation courses be incorporated by extension activities, especially the ones with significant relevance. In this article has been discussed proposals for the implementation of curriculum extension in Administration course at Universidade Federal do Pampa, a multicampi institution fonded in 2006 which has a goal of instigating the growth and development of south region in Rio Grande do Sul. The article is based on an exploratory research with qualitative approach characterized as a study case which using the documental analysis and interviews gathered data about extension in the institution, thus information about how the institutional governing body are being organized in order to accomplish the goals and how professors of other Campi and course apprehend the university extension, the curriculum extension goal and possible impacts. After analysing data, it was noticed that there is a lack of knowledge not only about curricularisation of extension, but also about university extension - even among extensionists. Several adjustments are required for the implementation of extension crediting in the course and in the institution. These changes were suggested in the work, however, it was not possible to define the best alternative indicated for the implemention of extension credited in the course.